Calendar anomalies in African stock markets - El Mehdi Ferrouhi; Omar Kharbouch; Samir Aguenaou; Muhammad Naeem (Cogent Economics & Finance, 2021)
In this paper, we investigate the day of the week and the month of the year effects in African stock markets, both in the Gregorian and the Hijri calendars. Specifically, we investigate Monday effect, Friday effect, January effect and Ramadan effect, from January 2009 to December 2019, using OLS regression with robust standard errors. January is the first month of the Gregorian calendar, while Ramadan is the 9th and the most sacred month of the lunar calendar, used in Muslim countries. The results obtained show the existence of Monday effect in BRVM and Namibia, Friday effect in Kenya and Namibia, January effect in Botswana and Zambia, December effect in Botswana, BRVM and Egypt and Ramadan effect in Tunisia.
Keywords: C22; G10; G11; G15; G17; 330; African stock markets; Day of the Week effect; DOW; Friday effect; January effect; Monday effect; Month of the Year effect; MOY; Ramadan effect